3D printed complete removable dental prostheses: a narrative review - Eva Anadioti; Leen Musharbash; Markus B. Blatz; George Papavasiliou; Phophi Kamposiora (BMC, 2020)
Abstract Background The purpose of this paper is to review the available literature on three-dimensionally printed complete dentures in terms of novel biomaterials, fabrication techniques and workflow, clinical performance and patient satisfaction. Methods The methodology included applying a search strategy, defining inclusion and exclusion criteria, selecting studies and forming tables to summarize the results. Searches of PubMed, Scopus, and Embase databases were performed independently by two reviewers to gather literature published between 2010 and 2020. Results A total of 126 titles were obtained from the electronic database, and the application of exclusion criteria resulted in the identification of 21 articles pertaining to printed technology for complete dentures. Current innovations and developments in digital dentistry have successfully led to the fabrication of removable dental prostheses using CAD/CAM technologies. Milled dentures have been studied more than 3D printed ones in the currently available literature. The limited number of clinical studies, mainly case reports, suggest current indications of 3D printing in denture fabrication process to be custom tray, record bases, trial, interim or immediate dentures but not definitive prostheses fabrication. Limitations include poor esthetics and retention, inability to balance occlusion and low printer resolution. Conclusions Initial studies on digital dentures have shown promising short-term clinical performance, positive patient-related results and reasonable cost-effectiveness. 3D printing has potential to modernize and streamline the denture fabrication techniques, materials and workflows. However, more research is required on the existing and developing materials and printers to allow for advancement and increase its application in removable prosthodontics.